Polyoxovanadate-modified SnO2 electron transport layer for perovskite photodetectors - Ziting Liu; Yijia Hao; Jing Zhang; Yi He; Weilin Chen (Polyoxometalates)
SnO2 is widely used in perovskite photodetectors as an electron transport layer material. The matching of the energy levels of SnO2 and perovskite is important in carrier transport. Polyoxovanadates (POVs), as semiconductor-like molecules, exhibit good redox and excellent optical properties, which can regulate the energy band structure of SnO2. Here, K5MnV11O32·10H2O (MnV11), K7MnV13O38·18H2O (MnV13), (NH4)8[V19O41(OH)9]·11H2O (V19), and K10[V34O82]·20H2O (V34) were used to modify an SnO2 colloidal solution. Energy level tests demonstrated that the conduction band potential (ECB) of MnV13-modified SnO2 increased from −4.43 to −4.03 eV, which matched more with the energy level of perovskite. This facilitated the extraction and transmission of photogenerated carriers. X-ray diffraction showed that POV-modified SnO2 exhibited better crystallinity. Scanning electron microscopy revealed that the grain size of perovskite increased to 580 nm after modification using MnV13. The final results showed that the MnV13-modified perovskite photodetector demonstrated the best efficiency. The photocurrent of the photodetector increased from 26 to 80 μA, and its stability was good. After 720 h, the normalized current values of unencapsulated devices on the MnV13@SnO2 substrate were maintained at more than 70% of the initial values. The study findings show that introducing POVs into photodetectors is a potential strategy for optimizing the performance of photovoltaic devices.